1989
DOI: 10.1002/bms.1200180207
|View full text |Cite
|
Sign up to set email alerts
|

Fast atom bombardment and fast atom bombardment collision-activated dissociation/mass-analysed ion kinetic energy analysis ofC-glycosidic flavonoids

Abstract: Fast atom bombardment (FAB) mass spectrometry and FAB tandem mass spectrometry in negative mode can provide molecular weight and very useful structural prior information for C-glycosyl flavonoids without derivatization. Diethaoolamine or thioglycerol matrix gave an abundant deprotonated molecular ion for all the studied compounds. Mass-analysed ion kinetic energy (MIKE) and collision-activated dissociation/MIKE spectra provide characteristic fragment ions which permit differentiation of the 6-and/or 8-location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
2
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 14 publications
8
67
2
2
Order By: Relevance
“…In another important fragmentation channel the ions at m/z 172 decompose even further, Le., by loss of 28 Da, due to secondary loss of CO, retaining only the C atom by which the hexose moiety is attached (Cl'). This transition is also reported as being pronounced in analogous flavone C-glycopyranosides (Becchi & Fraisse, 1989;Li et al, 1992;Prox, 1968).…”
Section: Resultsmentioning
confidence: 62%
“…In another important fragmentation channel the ions at m/z 172 decompose even further, Le., by loss of 28 Da, due to secondary loss of CO, retaining only the C atom by which the hexose moiety is attached (Cl'). This transition is also reported as being pronounced in analogous flavone C-glycopyranosides (Becchi & Fraisse, 1989;Li et al, 1992;Prox, 1968).…”
Section: Resultsmentioning
confidence: 62%
“…Deuterium labelling experiments indicated that hydroxyl hydrogen atoms are involved in the formation of Y n + ions [7]. Analogy exists for the MIKE/CID spectra obtained with negative ion FAB as described by Becchi and Fraisse [13]. In the spectra of the C-glycosides only the precursor …”
Section: Differentiation Between O-glycosides C-glycosides and O-c-dmentioning
confidence: 53%
“…These types of losses are well-known for C-glycosyl flavonoids, and were discussed in detail by Waridel et al [29]. The loss of one or more water molecules observed with some C-glycosyl flavonoid complexes has also been reported in mass spectral analysis of deprotonated C-glycosyl flavonoids [17,29,38] and alternate structures for these ions have been proposed [17].…”
Section: Resultsmentioning
confidence: 85%
“…Greater sensitivity has been reported in the negative ion mode than in the positive ion mode [21,30,31,38], a factor attributed to the substantial acidities of flavonoids and the ease of deprotonation due to their multiple hydroxyl groups. However, the CAD spectra of deprotonated flavonoid glycosides generally show few fragments, and are therefore not particularly useful for isomer differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation